Inflammation is associated to volume status in peritoneal dialysis patients. (3rd July 2015) - Unal, Aydin; Kavuncuoglu, Feridun; Duran, Mustafa; Oguz, Fatih; Kocyigit, Ismail; Sipahioglu, Murat Hayri; Tokgoz, Bulent; Oymak, Oktay
Abstract: Aim : The aim of this study is to investigate whether there is a relationship between inflammation and volume status in patients underwent peritoneal dialysis (PD). Patients and method : This cross-sectional study included 159 PD patients. The median duration of PD was 17 (range, 1–151) months. All patients were examined using bioelectrical impedance analysis to estimate the ratio of extracellular water to total body water (ECW/TBW), which was used to assess their volume status. The patients were categorized as having one of the following three volume statuses: hypervolemic (above +2 SD from the mean, which was obtained from healthy controls), normovolemic (between +2 SD and −2 SD), or hypovolemic (below −2 SD from the mean). Five patients with hypovolemia were excluded from the study. Fifty-six patients were hypervolemic whereas 98 patients were euvolemic. High-sensitive C-reactive protein (hs-CRP) levels were measured to evaluate inflammation in all patients. Results : hs-CRP value levels were significantly higher in hypervolemic patients compared with euvolemic patients [7.1 (3.1–44.0) mg/L vs. 4.3 (3.1–39.6), p : 0.015, respectively]. Left ventricular hypertrophy was more frequent in hypervolemic patients compared with euvolemic patients (53.6% vs. 30.6%, p : 0.004, respectively). ECW/TBW ratio positively correlated with hs-CRP ( r : 0.166, p : 0.039). Gender, hs-CRP, and residual Kt/V urea were found to be independent risk factors for hypervolemia in multivariate analysis. Conclusion : Inflammation is associated with hypervolemia in PD patients. Residual renal functions play an important role to maintain euvolemia in PD patients.